Exploring the Phenomenon of Using Social Media on Students' Religious Understanding in Polewali Mandar and Majene Regency (Alfred Schutz's Motive Perspective) - Muh. Ilham Usman; Muhammad Nur Murdan (Dinasti Publisher, 2025)
This article examines Exploring the Phenomenom of Using Social Media on Student’ Religious Understanding in Polewali Mandar dan Majene Regency, West Sulawesi. This study collected data through participant observation techniques and in-depth interviews with twenty students who became critical informants. This study used a qualitative method with Alfred Schutz's motive theory. The results of the study indicate that the use of social media among students has become a lifestyle. The use of social media has positive and negative aspects, as well as social media platforms (such as YouTube, Instagram, Facebook, and TikTok) to learn and understand religious and religious education. Using Alfred Schutz's motive theory, it was found that the reasons students use social media (because of motive) include seeking additional information about religious issues, finding out which religious lectures are popular, accessing religious lectures that are explained clearly and accurately on social media, and obtaining content quickly by clicking and listening to it satisfactorily. Students aim to achieve goals (in order to motive) by using social media, including using it as a source of self-introspection, understanding Islamic teachings in depth and detail, aspiring to become famous preachers, and listening to religious lectures as a necessity and entertainment in their free time.